To Dwell Is to Garden A History of Boston's Community Gardens - Bass Warner, Sam Jr (Northeastern University Press, 2019)
One of the more welcome changes in Boston's urban landscape has been the recent transformation of abandoned lots in to flourishing community gardens. In To Dwell Is to Garden, a distinguished scholar and a veteran photographer join forces to provide a history and a celebration of these urban oases and of the people who have made them possible. Sam Bass Warner, Jr., traces the origins of Boston's urban community gardens back to the English allotment gardens created to keep country folk from starving during the first great wave of urbanization. Warner suggests that today's urban community gardens owe their existence not to philanthropy or patriotism but to an activist impulse stemming from the civil rights movement, which emphasized self-help, local autonomy, and personal dignity to combat the problems of urban decay. The spirit of today's urban community gardens is captured in Hansi Durlach's compelling photographs of those individuals, young and old, who have worked together to clear the rubble and till the soil. From China and Chile, from Italy and Arkansas, from the suburbs and from next door, their comments, recorded by Durlach, linger in the mind and in the heart. Originally pubished by Northeastern University Press in 1987. With a new foreword by Jill Eshelman.